Pre-harvest effects on postharvest quality of spring-planted, day-neutral strawberries in high tunnel system - Gude, Kelly (Kansas State University, 2016)
Intensive specialty crop production within high tunnel systems in the central U.S. has greatly expanded. High tunnel systems, used primarily to protect specialty crops from harsh environmental conditions, improve marketability, and extend fruiting season. High tunnel day-neutral strawberry (Fragaria x ananassa) production in Kansas may by limited due to the high summer temperatures. Evaporative cooling within a high tunnel is a novel technique meant to cool the plant temperature during the hottest months of production. Currently, evaporative cooling is implemented in the early stages during the heavy bloom period. Spring-planted day-neutral strawberry production within high tunnels could provide growers with enhanced yields and marketability, improved storage quality, and late-season prices. This study identifies the optimum cultivars in a plasticulture, high tunnel system with the use of evaporative cooling in regards to yield, quality, storage life, and consumer opinion. The trial was conducted at the Kansas State University Olathe Horticulture Research and Extension Center (OHREC) during 2014 and 2015. Six commercially-available cultivars were evaluated: ‘Albion’, ‘Evie 2’, ‘Monterey’, ‘Portola’, ‘San Andreas’, and ‘Seascape’. Mature fruit (90-100% red) were harvested twice a week and four harvests were evaluated for at harvest and postharvest quality throughout each production year. Storage life was monitored every 24hrs by respiration rate, moisture content and overall visual quality, using a scale from 5 (excellent) to 1 (very poor). Physical and organoleptic quality measurements (texture and color, and soluble solids and titratable acidity) were evaluated every two days throughout storage, and nutritional quality (total phenolic and antioxidant availability) was evaluated at harvest. Our results indicate that ‘Portola’ had the highest yields in 2014 and 2015 at 1.33 lbs/plant and 1.12 lbs/plant, respectively. At harvest, the soluble solids content (°Brix) was highest with ‘Monterey’ and ‘Albion’ (P < 0.0001), while ‘San Andreas’, ‘Monterey’, ‘Portola’, and ‘Albion’ retained firm texture (force(g)) (P ≤ 0.0001). All cultivars maintained their overall visual quality until day 8, with the exception of ‘Evie 2’ and ‘Seascape’. Furthermore, the four cultivars maintained visual quality and had lower respiration rates and moisture content loss (P < 0.001, P < 0.0001, P < 0.05). Throughout storage, ‘Seascape’ had a high respiration rate (P < 0.0001) and low overall visual quality (P < 0.01). Moisture content loss (%) throughout 2014 storage life was less than in 2015 (P < 0.0001) and ‘San Andreas’ and ‘Monterey’ had the least moisture loss throughout both production seasons (P < 0.01). In our trials, evaporative cooling did not affect yield or the incidence of disease. However, the use of evaporative cooling resulted in lower total phenolic levels in both production years (P < 0.0001), and higher respiration rates during storage, as observed in 2015 (P ≤ 0.01). Because of significant year-to-year differences in berry weight (lbs/plant) and size (oz/fruit), further studies are needed to identify the weather effect and best management practices in the region. In Kansas, growing day-neutral strawberries in a high tunnel has potential based on yield and quality of the fruit that we evaluated.
Keywords: Evaporative cooling; Quality analysis; Health benefits